2019
DOI: 10.3390/joitmc5010017
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Social Enterprises with Organizational Culture, Network and Socioeconomic Performance: Latent Profile Analysis Approach

Abstract: Culture is a key driving force in enhancing organizational performance. The results of recent studies indicate the importance of managers having the capacity to understand organizational culture and link it to organizational performance improvement. This study aims to examine the relationship between organizational culture and performance improvement in social enterprises. In the past, organizational culture was described in terms of a single dimension, but it is now understood that different cultures reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…The analysis results showed that, firstly, the delivery system is more important than the administration or network in the social service system. As mentioned in many previous studies [58][59][60], the fact that the service delivery system is important in the area of social service or welfare service has been verified in this study as well. However, in this study, as compared to previous studies focusing on the integration of the delivery system, accessibility and participation possibility were considered the most important factors of the delivery system.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The analysis results showed that, firstly, the delivery system is more important than the administration or network in the social service system. As mentioned in many previous studies [58][59][60], the fact that the service delivery system is important in the area of social service or welfare service has been verified in this study as well. However, in this study, as compared to previous studies focusing on the integration of the delivery system, accessibility and participation possibility were considered the most important factors of the delivery system.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, activation of inter-organizational relationships is important for the provision of integrated service [56]. As part of the reorganization of the social welfare delivery system, governments are actively attempting to revitalize network cooperation between private and public institutions, that is, activating networking [57][58][59][60].…”
Section: Service Networkmentioning
confidence: 99%
“…As introduced earlier, unique for the present study is the combination of culture, social, environmental and economic outputs. Based on our exploratory factor analysis, the combination of measured items primarily from the original social and economic output constructs is perceived by employees as a single construct called socioeconomic performance, which is not a surprise as it is generally agreed that economic outputs and the delivery of social value comprise social enterprise performance [150]. For this reason, we name the new construct as "Socioeconomic Performance".…”
Section: Measured Itemsmentioning
confidence: 99%
“…Second, we use inductive qualitative analysis to assess the extent to which social trust facilitates collaborative efficiency through open innovation in informal economies. This contributes to the broader institution's literature (e.g., legal institutions and social institutions), extending understanding of how social trust accounts for entrepreneurial activities in informal economies and influences social and economies outcomes from entrepreneurship [30][31][32].…”
Section: Introductionmentioning
confidence: 83%